Evaluating Online Learning in Primary Education - Darmirah, Darmirah (Journal of Social Work and Science Education, 2022)
This study assesses the application of online learning in basic education at MIN 2 Palembang City using CIPP Model. This study employs a qualitative approach. Data reduction, data display, and making conclusions were used in the data analysis. The results found that the school environment is good, but the computer laboratory is non-existent due to restricted space. The examined aspect's input component is human resources, specifically students and instructors who support the adoption of online learning despite several barriers, including students' lack of psychological readiness for online learning and the lack of a computer laboratory. In the process component, it was determined that the implementation of learning was ineffective due to several hurdles such as internet network disruptions, device limits, quotas, economic situations, busy parents, and some subjects that were difficult to study online. The product component examines the learning outcomes in the form of leger. During the covid epidemic, assessment is less objective than in traditional learning.